The Relationship Between Entrepreneurship Education And Digital Literacy On Entrepreneurial Intention Through Self-Efficacy As An Intervening Variable - Mulyono, Lia Anggraini; Soetjipto, Budi Eko; Hermawan, Agus (International Education Trend Issues, 2023)
The purpose of this study was to determine the effect of entrepreneurship education and digital literacy on entrepreneurial intentions through self-efficacy in OTKP students at SMK in Mojokerto. The results showed that Entrepreneurship Education was proven to have a positive and significant influence on Self-Efficacy. In addition, Digital Literacy is also proven to affect Self-Efficacy positively and significantly. This study also successfully tested the mediating role of Self-Efficacy in the relationship between Entrepreneurship Education and Digital Literacy on Entrepreneurial Intention. The test results show that Self-Efficacy successfully mediates the effect of Entrepreneurship Education on Entrepreneurial Intention positively and significantly. In addition, the role of Self-Efficacy is also proven to be a positive and significant mediator of the effect of Digital Literacy on student entrepreneurial intention. Thus, the Self-Efficacy variable in this study shows its role as a mediator of independent variables that can increase the effect of Entrepreneurship Education and Digital Literacy on student entrepreneurial intention.